Gambaran Psychological Well-Being pada Pekerja Shift - I Putu Kreshna Fiyanta Putra; Budi Sarasati; Nurwahyuni Nasir (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aimed to describe the level of Psychological Well-Being among shift workers. Psychological Well-Being refers to an individual's ability to accept oneself, establish positive relationships with others, maintain autonomy, manage the environment effectively, have a sense of purpose in life, and continue personal growth. This study employed a quantitative approach with a descriptive research design. The participants consisted of 35 shift workers in Bekasi Regency selected through purposive sampling. Data were collected using the Ryff’s Scale of Psychological Well-Being, consisting of 18 items, and were analyzed using JASP software. The results indicated that the Psychological Well-Being of shift workers was in the moderate category, with a mean score of 59.69. These findings suggest that most shift workers were able to adapt to work demands and maintain adequate psychological functioning. The results are expected to serve as a reference for organizations in developing programs and policies aimed at enhancing employees' psychological well-being.